3‐O‐Sulfation of Heparan Sulfate Enhances Tau Interaction and Cellular Uptake. Issue 5 (10th December 2019) - Zhao, Jing; Zhu, Yanan; Song, Xuehong; Xiao, Yuanyuan; Su, Guowei; Liu, Xinyue; Wang, Zhangjie; Xu, Yongmei; Liu, Jian; Eliezer, David; Ramlall, Trudy F.; Lippens, Guy; et al.
Abstract: Prion‐like transcellular spreading of tau in Alzheimer's Disease (AD) is mediated by tau binding to cell surface heparan sulfate (HS). However, the structural determinants for tau–HS interaction are not well understood. Microarray and SPR assays of structurally defined HS oligosaccharides show that a rare 3‐ O ‐sulfation (3‐ O ‐S) of HS significantly enhances tau binding. In Hs3st1 −/− (HS 3‐ O ‐sulfotransferase‐1 knockout) cells, reduced 3‐ O ‐S levels of HS diminished both cell surface binding and internalization of tau. In a cell culture, the addition of a 3‐ O ‐S HS 12‐mer reduced both tau cell surface binding and cellular uptake. NMR titrations mapped 3‐ O ‐S binding sites to the microtubule binding repeat 2 (R2) and proline‐rich region 2 (PRR2) of tau. Tau is only the seventh protein currently known to recognize HS 3‐ O ‐sulfation. Our work demonstrates that this rare 3‐ O ‐sulfation enhances tau–HS binding and likely the transcellular spread of tau, providing a novel target for disease‐modifying treatment of AD and other tauopathies. Abstract : Strengthened interactions : The rare 3‐ O ‐sulfation (3‐ O ‐S) of heparan sulfate (HS) enhances the tau–HS interaction and cellular uptake of tau, suggesting an important role for 3‐ O ‐S in the transcellular spread of tau pathology in Alzheimer's disease (AD). This work suggests a novel strategy for disease‐modifying treatment of AD by targeting the tau/HS interface.